Correlates of Transactional Sex and Violent Victimization among Men Who Inject Drugs in Los Angeles and San Francisco, California - Walters, Suzan M. (J Urban Health, 2021)
Men who inject drugs (MWID) and engage in transactional sex (i.e., receive money or drugs in exchange for sex) are vulnerable to HIV and violence. However, MWID who engage in transactional sex have been less studied than women. We examine factors associated with transactional sex among MWID in Los Angeles and San Francisco and whether transactional sex is associated with violent victimization. MWID were recruited using targeted sampling methods in 2011–2013 and completed surveys that covered demographics, drug use, HIV risk, violence, transactional sex, and other items. Multivariable logistic regression was used to (1) determine factors independently associated with transactional sex and (2) determine if transactional sex was independently associated with violence victimization in the last 6 months among MWID. An interaction term between income source and sexual identity was included in the transactional sex model. Of the 572 male PWID in the sample, 47 (8%) reported transactional sex in the past 6 months. Self-reported HIV infection was 7% for MWID who did not report transactional sex, 17% for MWID who reported transactional sex, and 24% for MWID who reported transactional sex and reported gay or bisexual identity. In multivariable analysis, transactional sex was positively associated with gay or bisexual identity (GB without illegal income adjusted odds ratio [AOR] = 5.16; 95% confidence interval [CI] = 1.86–14.27; GB with illegal income AOR = 13.55, CI = 4.57–40.13), coerced sex in the last 12 months (AOR = 11.66, CI = 1.94–70.12), and violent victimization in the last 12 months (AOR = 2.31, CI = 1.13–4.75). Transactional sex was negatively associated with heroin injection (last 30 days) (AOR = 0.37; 95% CI = 0.18–0.78). Transactional sex was independently associated with violent victimization in the last 12 months (AOR = 2.04; 95% CI = 1.00–4.14) while controlling for confounders. MWID who engaged in transactional sex are at elevated risk for HIV and multiple forms of violent victimization. Interventions focused on this at-risk subpopulation are urgently needed and should include access to substance use disorder treatment, victimization services, and harm reduction services across the HIV care continuum.